2009
DOI: 10.1038/ngeo468
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Climate and human influences on global biomass burning over the past two millennia

Abstract: In this Article, the y axis label of Fig. 4d was incorrect; it should have read 'Population (10 6)'. This has been corrected in the HTML and PDF versions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…Our study together with others show the prevalence of positive fire-vegetation feedbacks in communities dominated by taxa that did not evolve with a high fire frequency (McWethy et al, 2010;Perry et al, 2012). These systems are, in the context of climatic changes and anthropogenic increases in ignition, prone to suffer rapid landscape transformations (Bowman et al, 2011;Kitzberger et al, 2016;Marlon et al, 2009;McWethy et al, 2013;Miller et al, 2005;Veblen & Lorenz, 1988). Neglecting the effect of humans in enhancing firevegetation feedbacks can have catastrophic effects on fire regimes and cause irreversible changes in landscapes.…”
Section: Discussionsupporting
confidence: 55%
“…Our study together with others show the prevalence of positive fire-vegetation feedbacks in communities dominated by taxa that did not evolve with a high fire frequency (McWethy et al, 2010;Perry et al, 2012). These systems are, in the context of climatic changes and anthropogenic increases in ignition, prone to suffer rapid landscape transformations (Bowman et al, 2011;Kitzberger et al, 2016;Marlon et al, 2009;McWethy et al, 2013;Miller et al, 2005;Veblen & Lorenz, 1988). Neglecting the effect of humans in enhancing firevegetation feedbacks can have catastrophic effects on fire regimes and cause irreversible changes in landscapes.…”
Section: Discussionsupporting
confidence: 55%
“…For example, it is shown that the mean sea level over the South China Sea has a rise rate of 11.3 mm/yr during 1993-2000 and a fall rate of 11.8 mm/yr during -2005[Cheng and Qi, 2007. For the northeast coast of the United States, a collection of model projections have shown a rapid SLR in the next century, and the rise could have a greater effect on the heavily populated coastal regions than estimated previously [Yin et al, 2009]. A recent review has concluded that improving estimates of the spatial variability in future sea level changes should be an important research target in coming years [Milne et al, 2009].…”
Section: Introductionmentioning
confidence: 94%
“…[4] Ocean models have been the primary tools in quantifying sea level changes and project the 21st century sea level rise as well as estimate ocean heat content [Wunsch et al, 2007;Yin et al, 2009;Gregory et al, 2004]. However, most of these ocean models are designed to conserve volume rather than mass [e.g., Haidvogel and Beckmann, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…Database (e.g., Daniau et al, 2012;Marlon et al, 2016;Power et al, 2008;Vannière et al, 2016;Marlon et al, 2008) have focused on grassland systems. In part, this is due to the difficulties in identifying which sites should be considered "grassland" given that they can be defined in many ways and their spatial distributions vary through time.…”
Section: Global Charcoal Database and Grassland Biomesmentioning
confidence: 99%